Hormone Exposure During Pregnancy and Maternal Care - Lockyer, Rachel B. (East Carolina University, 2015)
It is suspected that prenatal hormones can affect maternal care, which has important implications for the neurological development of pups. To determine if the altered hormone levels affected maternal care, pregnant dams were exposed to sex hormones and maternal care behavior was quantified and analyzed. Pregnant dams were exposed to corn oil (solvent control), 50ug/kg of estradiol benzoate, or 8mg/kg dihydrotestosterone propionate from gestational day 15.5 to 17.5 which corresponds with a specific developmental window of neurological development. Maternal care during postnatal days 7 and 14 was recorded using JWatcher software and analyzed using R statistical software. No statistically significant differences were found among the treatment groups; however, there was an interesting variation seen in the results. There are many different possibilities for why I saw no significant effects. For example, I only dosed animals for three days. The variation in response to sex hormone exposure suggests that females respond differently to hormone exposure and this idea would be interesting to study further.
Keywords: hormones; hormone exposure; maternal care